The Cleaved Peptide of PAR1 Results in a Redistribution of the Platelet Surface GPIb-IX-V Complex to the Surface-Connected Canalicular System - Furman, Mark I.; Nurden, Paquita; Berndt, Michael C.; Nurden, Alan T.; Benoit, Stephen E.; Barnard, Marc R.; Ofosu, Frederick A.; Michelson, Alan D. (Thrombosis and Haemostasis, 2000)
The only known function of the 41 amino acid cleaved peptide (TR1-41) of the seven transmembrane domain thrombin receptor (PAR1) is to activate platelets (as determined by aggregation, surface P-selectin, and fibrinogen binding to activated GPIIb-IIIa). We now demonstrate that TR1-41 results in a concentration-dependent decrease in the platelet surface expression of each component of the GPIb-IX-V complex, as determined by flow cytometry with a panel of monoclonal antibodies (including 6D1, directed against the von Willebrand factor binding site on GPIbα, and TM60, directed against the thrombin binding site on GPIbα). TR1-41 also decreased ristocetin-induced platelet agglutination. Immunoblotting after incubation of platelets with TR1-41 revealed neither a loss of platelet GPIb nor increase in supernatant GPIb fragments. As demonstrated by immunoelectron microscopy, TR1-41 resulted in a redistribution of GPIb, GPIX, and GPV from the platelet surface to the surface-connected canalicular system (SCCS). In summary, the cleaved peptide (TR1-41) of PAR1 results in a redistribution of the platelet surface GPIb-IX-V complex to the SCCS, thereby negatively regulating the GPIbα binding sites for von Willebrand factor and thrombin.
Keywords: Thrombin; thrombin receptor; von Willebrand factor; peptide; flow cytometry